ANALISIS INTERAKSI GURU DAN SISWA DALAM PEMBELAJARAN IPA MATERI EKOSISTEM FASE C DI SDN 01 TEGALONTAR - Indra Surya, Bima; Sahrul Akmal Mufti; Rolanda Guruh Widyanto; Finka Putri Shoumi; Nurlaila Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine how teachers and students interact during science learning with the material ecosystem at SDN 01 Tegalontar in Phase C. Good interaction during learning is crucial to increase student participation, enthusiasm, and understanding of the material being studied. This study used qualitative and descriptive methods. Data were collected through literature review, observation, and interviews with teachers and students participating in the teaching and learning process. Data were analyzed using qualitative descriptive methods and source triangulation to ensure data accuracy. The results showed that the relationship between teachers and students in science learning was well-established, but student engagement levels varied. Some students became more active when learning was connected to real-life experiences and environmental observation activities, while others tended to remain passive. Differences in students' learning styles, such as visual, auditory, and kinesthetic, also influenced their engagement in the learning process. Teachers have attempted to create interaction through questions and answers and discussions, but more varied and student-focused learning methods are needed to increase participation in learning. In this way, understanding student characteristics and using interactive learning methods can improve the quality of interactions and increase the effectiveness of science learning in elementary schools.